Tax Avoidance and Corporate Risk in Indonesia: The Role of Tax Risk and Executive Characteristics - Carolina, Verani; Dewi, Nunik Lestari; Asher, Steven (Jurnal Akuntansi AKUNESA, 2024)
This study aims to examine the impact of tax avoidance on corporate risk, utilizing tax risk and executive characteristics as moderating factors. Those in executive positions are perceived to exert influence over their decisions, including those pertaining to the avoidance of taxes, which could be considered a risky decision. The study utilizes ten years of data to analyze the long-term tax avoidance patterns of non-financial Indonesian companies. The findings reveal that over the long run, tax avoidance practices can amplify a corporate's risk, and that tax risk and executive characteristics have been shown to intensify the impact of tax avoidance on corporate risk.